Efeito da cocultura sem contato de astrócitos tratados com ácidos graxos saturados com neurônios hipotalâmicos - Melo, Nayara de Freitas Martins (2014)
A fatty high diet causes inflammation in the hypothalamus, mainly in the neurons that control satiety and thermogenesis. Moreover, activation of apoptosis via TLR4 (toll like receptor 4) is observed in conjunction with inflammatory condition. The neuronal death is a process that involves the release of cytokines and glial activation. The microglia have immune function in nervous tissue, but the astrocytes, the main component of glia, is more involved in synaptic plasticity and chronic responses of the Central Nervous System. Moreover, these cells in the hypothalamus, which is the center of energy metabolism control, have specific characteristics, with receptors for fatty acids, glucose and leptin. In this context, we investigated the response of astrocytes after in vitro treatment with fatty acids on cortical and hypothalamic astrocytes. To that end, we made the dissociation of the cortex and hypothalamus of Swiss mice (1-2 days) and the cells were plated for procedures. Treatments were performed with different doses of stearate (100μM, 200μM and 2mM) and palmitate (200μM, 500μM and 5mM) for one week. Immunocytochemistry was performed with anti-GFAP (evaluates the astroglial reactivity) and anti-NFB (transcription factor that participates in the TLR-4 pathway) and TNF- dosage by ELISA. Dosage of 200μM medium were reserved after 3 days of contact with astrocytes that were treated with palmitate or stearate, for obtaining conditioned medium that were stocked for neurons culture treatment. Cultures of hypothalamic neurons (lineage CLU189) were treated for 3 or 6 days with conditioned medium, in sequence, in this cultures, were performed immunocytochemistry with caspase3 (apoptosis marker) and anti- Ki-67 (cell proliferation marker). The immunostaining was quantified and statistically treated for comparison of experimental and control groups. The results showed that treatment with stearate enhances the expression of GFAP and NFB only in astrocytes from the hypothalamus. The TNF- was upregulated in conditionated medium used for treatment of hypothalamic cells, however this augment did not interfere with apoptosis rate in CLU 189 cultures in first three days of contact with conditionated medium and, in the sixth day, in comparison to conditioned control medium only in astrocytes. Such results showed the protection provided for substances had released by reactived astrocytes from hypothalamus. Also, our results showed that neurons could respond to fatty acid without other cell intervention.